What happens before and after midnight A study on social culture of dating in Tacloban City. - Briones, Niña Arlyn L.; Caducoy, Carmela B.; Gonzales, Amiel Tristan (Tacloban City Niña Arlyn L. Briones, 2010)
This research is an exploration of the Dating culture based on Nightlife activities observed and practiced by a sample of Teens within Tacloban City. Data was gathered through a two-step process: (a) Survey to determine the age, nightlife activities and preferences of 300 sampled respondents using a 10-item questionnaire and (b) in -depth interview of 20 respondents to determine dating activities, reasons, relationships formed, problems and factors influencing dating culture. A sample of Registered Bars, Restaurants, Eateries, Coffee shops and other related establishments served as research locale. Results show that a significant number of active date goers is between ages of 19-21 years and majority of which are women. The common dating places of teens include Astrodome, Magsaysay Boulevard and Cueballs. Researchers identified and distinguished two major types of dating: group and exclusive. Majority of the respondents identified recreation and need for group interaction as their primary reasons for dating yet considers dating as a possible avenue for mate selection as well. Peer influence plays the most significant factor in an individual's dating behavior and attitude over family and media. Romantic and peer relationships are the most common relationship that develops from dating; however, sexual relationships while romantic and sexual relations are usually short-term types. The dating culture among teens within Tacloban City follows the trends observed by stereotypical urban communities. It is postulated that an indirect relationship between Dating activities activities and the emergence of other social issues such as pre-marital sex, early marriages and youth rebellion towards parents do exist.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban.
Keywords: Social Science